2010
DOI: 10.1111/j.1365-294x.2010.04745.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring landscape effects on gene flow: a new model selection framework

Abstract: Populations in fragmented landscapes experience reduced gene flow, lose genetic diversity over time and ultimately face greater extinction risk. Improving connectivity in fragmented landscapes is now a major focus of conservation biology. Designing effective wildlife corridors for this purpose, however, requires an accurate understanding of how landscapes shape gene flow. The preponderance of landscape resistance models generated to date, however, is subjectively parameterized based on expert opinion or proxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
390
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(409 citation statements)
references
References 55 publications
11
390
1
Order By: Relevance
“…As shown in this study, connectivity models and the corridors suggested by them depend strongly on the analytical methods used for creating and utilizing underlying resistance surfaces. Several published studies have suggested ways for finding optimal resistance values (e.g., Kuroe et al 2011, Shirk et al 2010, Graves et al 2014, and these studies have certainly improved resistancebased connectivity modeling. However, the effects of different conceptual approaches underlying resistance models (habitat suitability vs. resistance to inter-population movement) or the analytical choices made during their creation and analysis (additive vs. multiplicative models, least-cost vs. circuit-theory) appear to be at least as important as the numerical optimization of resistance values.…”
Section: Implications For Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in this study, connectivity models and the corridors suggested by them depend strongly on the analytical methods used for creating and utilizing underlying resistance surfaces. Several published studies have suggested ways for finding optimal resistance values (e.g., Kuroe et al 2011, Shirk et al 2010, Graves et al 2014, and these studies have certainly improved resistancebased connectivity modeling. However, the effects of different conceptual approaches underlying resistance models (habitat suitability vs. resistance to inter-population movement) or the analytical choices made during their creation and analysis (additive vs. multiplicative models, least-cost vs. circuit-theory) appear to be at least as important as the numerical optimization of resistance values.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Specifically, we used genetic samples of brown bears genotyped at 17 polymorphic microsatellite loci to quantify genetic structure and measured the genetic distance among samples as the proportion of shared alleles (Bowcock et al 1994). The relationship between the genetic structure observed within the bear population and likely drivers of landscape resistance was systematically evaluated through v www.esajournals.org reciprocal causal modeling (Cushman et al 2006(Cushman et al , 2013b and the multi-model optimization approach developed by Shirk et al (2010). The resulting resistance models included variables of landscape composition (percentage of landscape cover by mixed forest and agricultural lands), landscape configuration (cohesion of mixed forest and shrubland) and canopy cover.…”
Section: Landscape Resistance Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This high resistance value is used because, given roads are narrow (only 2-3 pixels wide in most cases), animals will encounter roads only for a short distance. Moreover, empirical studies (e.g., Shirk et al 2010 for mountain goats) have found similarly high relative resistances for roads, and although responses to roads will be species-specific, the logic of using values which are orders of magnitude higher than other resistance values is consistent. Road resistance values of similar magnitude were used for mammalian connectivity modeling by the Washington Habitat Connectivity Working Group (WHCWG 2010).…”
Section: Compositional Analysismentioning
confidence: 87%
“…To circumvent this problem, methods are needed to provide truly empirical movement resistance estimates. Recent studies have attempted to estimate resistance by comparing model fit to real data [17][18][19]. Recently, Driezen et al [20] presented a method of validating the best least-cost path tested model with real dispersal paths, and reiterated the necessity to work with habitat specialist species to estimate cost values throughout the landscape.…”
Section: Introductionmentioning
confidence: 99%